Porous carbon particles with high ethane selectivity and preparation method thereof

By using coconut-based activated carbon as a carbon source and combined with microwave catalytic technology, porous carbon particles with high ethane selectivity were prepared, which solved the problem of low ethane/ethylene adsorption selectivity of existing materials, achieved efficient ethane/ethylene gas separation, and had good industrial application prospects.

CN119819259APending Publication Date: 2025-04-15GUANGZHOU UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510214500.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing ethylene/ethane adsorption separation materials have low adsorption selectivity for ethane/ethylene and have not yet met the requirements for industrial applications.

Method used

Highly ethane-selective porous carbon particles are prepared by microwave catalytic technology using low-priced coconut shell-based activated carbon as the carbon source. The method includes crushing and screening of coconut shell activated carbon, washing and drying treatment, followed by carbonization and activation in a silicon carbide crucible to form porous carbon particles.

Benefits of technology

The prepared porous carbon particles have high ethane adsorption selectivity and excellent ethane adsorption capacity. They are suitable for fixed bed adsorption and separation of ethane/ethylene gas, and have good industrial application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819259A_ABST
    Figure CN119819259A_ABST
Patent Text Reader

Abstract

The invention relates to the field of adsorption materials, in particular to porous carbon particles with high ethane selectivity and a preparation method thereof.The preparation method comprises the following steps that 1, coconut shell activated carbon particles are prepared, specifically, blocky industrial coconut shell activated carbon is taken to be smashed, and screening, washing, filtering and drying treatment are conducted in sequence to obtain the coconut shell activated carbon particles; the coconut shell activated carbon particles are uniform in particle size; and step 2, preparation of porous carbon particles: putting the coconut shell activated carbon particles into a silicon carbide crucible, putting the silicon carbide crucible into a microwave catalysis instrument, and carrying out an activation reaction in a carbon dioxide atmosphere to obtain the porous carbon particles. The porous carbon particles disclosed by the invention have the characteristic of high ethane adsorption selectivity: under the conditions of 25 DEG C and 1.0 bar, the adsorption capacity of the porous carbon particles to ethane is 3.07 mmol / g, and the adsorption selectivity of the porous carbon particles to equimolar ethane / ethylene mixed gas is as high as 3.97, which is higher than that of most powdery adsorption materials reported in current literatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of adsorption materials, and in particular to porous carbon particles with high ethane selectivity and a preparation method thereof. Background Art

[0002] Ethylene is a major product of petrochemical industry, and ethylene and its derivatives account for more than 70% of global petrochemical products. Since the physical properties of ethylene and ethane are very similar, in order to obtain high-purity ethylene, the industry currently mainly uses high-pressure and low-temperature distillation technology to separate ethylene / ethane from cracking gas. This is an energy-intensive and capital-intensive separation process. Ethylene is the petrochemical product with the largest energy consumption and carbon dioxide emissions after synthetic ammonia. Adsorption separation method is considered to be a highly promising ethylene / ethane efficient separation technology due to its advantages such as mild operating conditions, low energy consumption, relatively simple separation process and large operational flexibility. Adsorption material is the core of adsorption separation method, and the design and preparation of adsorption materials with stable structure, high selectivity and capacity are the key.

[0003] For the adsorption separation of ethylene / ethane mixed gas, adsorption materials can be divided into two types: one is ethylene selective adsorption material, and the other is ethane selective adsorption material. For the development of ethylene selective adsorption material, the principle that ethylene with carbon-carbon double bonds can easily form π bonds with some transition metals in a reduced state is mainly used to introduce reduced metal ions (such as Cu + 、Ag + etc.), developed adsorbents that can form π bonds with ethylene molecules and have the characteristic of preferentially adsorbing ethylene. The characteristic of these adsorbents is that they have high selectivity for ethylene / ethane adsorption separation. However, researchers have also found that the separation process of ethylene and ethane from industrial cracking gas using ethylene selective adsorption materials is still relatively complicated and economically unfeasible. This is because: (1) Ethylene is the main component in industrial cracking gas, with a content of up to 90%. If ethylene selective adsorbents are used, a large amount of adsorbent and a larger volume of adsorption bed are required; (2) The target product ethylene needs to be obtained by desorption. Since the π bond formed by ethylene and the adsorbent is a weak chemical bond, the desorption energy consumption is very high; even more fatally, to obtain polymerization-grade standard ethylene (purity of 99.95%), at least four adsorption-desorption cycles are required, which leads to a relatively complicated separation process and high energy consumption. In sharp contrast, if ethane selective adsorbent is used to separate ethylene / ethane from cracking gas, it is only necessary to remove low-content ethane in the cracking gas through an adsorption process to obtain high-purity ethylene directly at the outlet, which greatly simplifies the separation process and reduces separation energy consumption, making it more economical.

[0004] Therefore, the study of ethane selective adsorption materials has become a topic with greater scientific significance and practical needs. The inherent advantages of carbon materials, such as stable structure, easy molding and relatively low preparation cost, make them have good prospects for industrial application. In the field of adsorption and separation of ethylene / ethane mixed gases, ethane selective carbon adsorption materials have also emerged. Researchers have found that the selection of new carbon sources can prepare new porous carbon materials with high ethane adsorption capacity. Studies have shown that carbon materials have considerable adsorption capacity for ethane gas. However, the bottleneck problem that currently restricts the application of carbon materials is that the adsorption selectivity of carbon materials for ethane / ethylene is still relatively low, and there is still a certain gap from the selectivity requirements for industrial applications. This is a difficult problem that urgently needs to be solved and broken through.

[0005] In order to produce a shaped carbon-based adsorption material with high ethane / ethylene adsorption selectivity, stable material structure and more economical cost, this project invented a method of using coconut shell-based activated carbon with low market price as a carbon source to prepare a porous carbon particle with high ethane selectivity. This material has high ethane adsorption selectivity, excellent ethane adsorption capacity, and uniform particle morphology, and has great industrial application value in fixed bed adsorption and separation of ethane / ethylene gases. Summary of the invention

[0006] In view of the problems existing in the prior art, the object of the present invention is to provide a porous carbon particle with high ethane selectivity and a preparation method thereof. Compared with the currently reported ethane / ethylene adsorption separation materials, the present invention provides a porous carbon particle with high ethane adsorption selectivity, excellent ethane adsorption capacity, and uniform particle morphology and a preparation method thereof.

[0007] The purpose of the present invention is achieved by the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing porous carbon particles with high ethane selectivity, comprising the following steps:

[0009] Step 1, preparation of coconut shell activated carbon particles:

[0010] The industrial coconut shell activated carbon in block form is crushed, and then screened, washed, filtered and dried to obtain coconut shell activated carbon particles with uniform particle size;

[0011] Step 2, preparation of porous carbon particles:

[0012] The coconut shell activated carbon particles are placed in a silicon carbide crucible, put into a microwave catalyst instrument, and activated in a carbon dioxide atmosphere to obtain porous carbon particles.

[0013] Preferably, in step 1, screening is performed by using sieve plates with mesh sizes of 300 μm and 250 μm to screen the crushed coconut shell activated carbon particles, and retaining coconut shell activated carbon particles with a particle size between 250-300 μm.

[0014] Preferably, in step 1, washing is to wash the screened particles with deionized water for 3 times, and filtering is to collect the solid particles by filtering after washing.

[0015] Preferably, in step 1, the drying is carried out in a forced air drying oven at 100° C. for 10 hours.

[0016] Preferably, in step 2, before the activation reaction is carried out, 100-300 mL / min carbon dioxide gas is used to purge the cavity of the instrument for 20 minutes.

[0017] Preferably, in step 2, the output power during the activation reaction is 500-800 W, and the microwave irradiation time is 10-30 min.

[0018] In a second aspect, the present invention provides porous carbon particles with high ethane selectivity, which are prepared by the above method.

[0019] In a third aspect, the present invention provides a porous carbon particle with high ethane selectivity for use in the adsorption and separation of ethane / ethylene mixed gas.

[0020] Preferably, the porous carbon particles have the characteristic of preferentially adsorbing ethane. Under the conditions of 25° C. and 1.0 bar, the adsorption selectivity of the porous carbon particles for an equimolar ethane / ethylene mixed gas is as high as 3.97, and the adsorption capacity for ethane reaches 3.07 mmol / g.

[0021] The beneficial effects of the present invention are:

[0022] (1) The porous carbon particles prepared by the present invention have high ethane adsorption selectivity, excellent ethane adsorption capacity, and uniform particle morphology, and have good industrial application value in fixed-bed adsorption separation of ethane / ethylene gases.

[0023] (2) The raw materials used in the present invention are industrial coconut shell-based activated carbon and carbon dioxide gas with low market prices, and the raw material prices are economical; the carbonization activation process is carried out in a microwave catalyst instrument, with low output power and short preparation time; the entire preparation process is simple, easy to implement, and highly repeatable. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The present invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the present invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.

[0025] Figure 1 Nitrogen adsorption isotherms of the porous carbon particles prepared in Examples 1-5 and the material prepared in the comparative example at -196°C.

[0026] Figure 2 The adsorption isotherms of ethane at 25°C for the porous carbon particles prepared in Examples 1-5 and the material prepared in the comparative example.

[0027] Figure 3 The adsorption isotherms of ethylene for the porous carbon particles prepared in Examples 1-5 and the materials prepared in the comparative example at 25°C.

[0028] Figure 4 IAST adsorption selectivity of the porous carbon particles prepared in Examples 1-5 and the materials prepared in the comparative example for equimolar ethane / ethylene mixed gas at 25°C.

[0029] Figure 5 The IAST adsorption selectivity and ethane adsorption capacity of the porous carbon particles prepared in Examples 3-5 for equimolar ethane / ethylene mixed gas at 25°C are compared. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is described below through specific examples. It should be understood that the one or more method steps mentioned in the present invention do not exclude the existence of other method steps before and after the combination step or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to limit the scope of the present invention. The change or adjustment of the relative relationship thereof shall also be regarded as the scope of the present invention without substantially changing the technical content.

[0031] In order to better understand the above technical scheme, the exemplary embodiments of the present invention are described in more detail below. Although exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0032] The present invention will be further described below in conjunction with the following examples.

[0033] Example 1

[0034] (1) Weigh 5.0 g of industrial coconut shell activated carbon in block form and crush it. Use sieve plates with mesh sizes of 300 μm and 250 μm to screen the crushed coconut shell activated carbon particles to obtain coconut shell activated carbon particles with a particle size of 250-300 μm. Then use 500 mL of deionized water to wash the coconut shell activated carbon particles three times, filter them, and dry them in a 100° C. forced air drying oven for 10 hours to obtain coconut shell activated carbon particles with uniform particle size.

[0035] (2) The coconut shell activated carbon particles were placed in a silicon carbide crucible, which was then placed in a microwave catalytic instrument. The instrument cavity was purged with 100 mL / min of carbon dioxide gas for 20 min. The microwave catalytic instrument was then started with an output power of 500 W and a microwave irradiation time of 10 min to obtain porous carbon particles, which were recorded as material 1#.

[0036] Example 2

[0037] (1) Same as Example 1;

[0038] (2) The coconut shell activated carbon particles were placed in a silicon carbide crucible, which was then placed in a microwave catalytic instrument. 150 mL / min of carbon dioxide gas was used to purge the instrument cavity for 20 min. The microwave catalytic instrument was then started with an output power of 700 W and a microwave irradiation time of 10 min to obtain porous carbon particles, which were recorded as material 2#.

[0039] Example 3

[0040] (1) Same as Example 1;

[0041] (2) The coconut shell activated carbon particles were placed in a silicon carbide crucible, which was then placed in a microwave catalytic instrument. The instrument cavity was purged with 200 mL / min of carbon dioxide gas for 20 min. The microwave catalytic instrument was then started with an output power of 800 W and a microwave irradiation time of 15 min to obtain porous carbon particles, which were recorded as material 3#.

[0042] Example 4

[0043] (1) Same as Example 1;

[0044] (2) The coconut shell activated carbon particles were placed in a silicon carbide crucible, which was then placed in a microwave catalytic instrument. The instrument cavity was purged with 300 mL / min carbon dioxide gas for 20 min. The microwave catalytic instrument was then started with an output power of 800 W and microwave irradiation time of 20 min to obtain porous carbon particles, which were recorded as material 4#.

[0045] Example 5

[0046] (1) Same as Example 1;

[0047] (2) The coconut shell activated carbon particles were placed in a silicon carbide crucible, which was then placed in a microwave catalytic instrument. The instrument cavity was purged with 300 mL / min carbon dioxide gas for 20 min. The microwave catalytic instrument was then started with an output power of 800 W and microwave irradiation time of 30 min to obtain porous carbon particles, which were recorded as material 5#.

[0048] Comparison Example

[0049] The control example is a block of industrial coconut shell activated carbon without any treatment, which is recorded as material 0#.

[0050] Experimental example

[0051] In order to illustrate the structural characteristics and ethane / ethylene adsorption performance of the porous carbon particles 1#-5# prepared in each example, we characterized the pore structure and evaluated the ethane / ethylene adsorption separation performance of the material 0# and porous carbon particles 1#-5# of the control example.

[0052] The pore structure characterization was carried out on a Micromeritics 3Flex three-station all-purpose gas adsorption instrument. The nitrogen adsorption curve of the material at -196°C (the test interval was relative pressure P / P0<0.35) was tested and the BET specific surface area of ​​the material was obtained by applying the built-in analysis method. The adsorption performance of ethane and ethylene was evaluated by using a Micromeritics 3Flex three-station all-purpose gas adsorption instrument to measure the adsorption isotherms of ethane and ethylene of material 0# and porous carbon particles 1#-5# at 25°C. The adsorption selectivity of porous carbon particles 1#-5# for equimolar ethane / ethylene mixed gas is based on the adsorption isotherm data of the above-mentioned materials for ethane and ethylene at 25°C, and is calculated by ideal adsorption solution theory (IAST). This adsorption selectivity is called IAST adsorption selectivity. The results are as follows:

[0053] Figure 1 The nitrogen adsorption isotherms of porous carbon particles 1#-5# prepared in the examples and material 0# prepared in the control example at -196°C. Compared with material 0#, the nitrogen adsorption amount of porous carbon particles 1#-5# in the low pressure range increases significantly with the increase of pressure, indicating that porous carbon particles 1#-5# have rich porous structures. The BET specific surface area of ​​the material is obtained by applying the built-in analysis method, which is listed in Table 1.

[0054] Table 1 Specific surface area, ethane and ethylene adsorption capacity and IAST adsorption selectivity of porous carbon particles

[0055]

[0056] Note: a: 25°C and 1.0 bar; b: 25°C and 1.0 bar, and an equimolar ethane / ethylene mixture.

[0057] Combined with the preparation conditions of the embodiment, it is found that with the increase of the output power of the microwave catalytic instrument and the extension of the microwave irradiation time, the pore structure of the prepared porous carbon particles is more developed, and the BET specific surface area of ​​the porous carbon particles 5# reaches 459.7 m 2 This also shows that the microwave-assisted carbonization activation method provided by the present invention is an effective method for preparing porous carbon materials with developed pore structures.

[0058] Figure 2 and Figure 3 The adsorption isotherms of porous carbon particles 1#-5# prepared in the examples and material 0# prepared in the control example for ethane and ethylene at 25°C are shown in Figures 1-5. By comparison, it is found that under the same conditions, the adsorption capacity of porous carbon particles for ethane is higher than that for ethylene, indicating that the porous carbon particles developed in this patent have the characteristic of preferentially adsorbing ethane, and the adsorption capacity of porous carbon particle 5# for ethane at 25°C and 1.0 bar reaches 3.07 mmol / g.

[0059] Figure 4 The IAST adsorption selectivity of porous carbon particles 1#-5# prepared in the examples and material 0# prepared in the control example for equimolar ethane / ethylene mixed gas at 25°C. As can be seen from the figure, the IAST adsorption selectivity of porous carbon particles 1#-5# for equimolar ethane / ethylene mixed gas gradually decreases with the increase of the mixed gas pressure. Figure 4 and Figure 5 It can be seen from the combination that at 25°C and 1.0 bar, the adsorption capacity of porous carbon particle 5# for ethane is 3.07 mmol / g, and the adsorption selectivity of porous carbon particle 4# for equimolar ethane / ethylene mixed gas is as high as 3.97, which is higher than the adsorption selectivity of most porous carbon materials for ethane / ethylene mixed gas reported in the literature.

[0060] The above results show that the porous carbon particles prepared in the present invention have high ethane adsorption selectivity, excellent ethane adsorption capacity, and uniform particle morphology, and have good industrial application prospects in fixed-bed adsorption separation of ethane / ethylene gases.

[0061] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms should not be understood as necessarily being directed to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification.

[0062] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing porous carbon particles with high ethane selectivity, characterized in that: The following steps are involved: Step 1, preparation of coconut shell activated carbon particles: The industrial coconut shell activated carbon in block form is crushed, and then screened, washed, filtered and dried to obtain coconut shell activated carbon particles with uniform particle size; Step 2, preparation of porous carbon particles: The coconut shell activated carbon particles are placed in a silicon carbide crucible, put into a microwave catalyst instrument, and activated in a carbon dioxide atmosphere to obtain porous carbon particles.

2. The method for preparing porous carbon particles with high ethane selectivity according to claim 1, characterized in that: In the step 1, screening is performed by using sieve plates with mesh sizes of 300 μm and 250 μm to screen the crushed coconut shell activated carbon particles, and retaining coconut shell activated carbon particles with a particle size between 250-300 μm.

3. The method for preparing porous carbon particles with high ethane selectivity according to claim 1, characterized in that: In the step 1, washing is to wash the screened particles with deionized water for 3 times, and filtering is to collect the solid particles by filtering after washing.

4. The method for preparing porous carbon particles with high ethane selectivity according to claim 1, characterized in that: In the step 1, the drying is carried out in a forced air drying oven at 100° C. for 10 hours.

5. The method for preparing porous carbon particles with high ethane selectivity according to claim 1, characterized in that: In the step 2, before the activation reaction is carried out, 100-300 mL / min of carbon dioxide gas is used to purge the cavity of the instrument for 20 minutes.

6. The method for preparing porous carbon particles with high ethane selectivity according to claim 1, characterized in that: In step 2, the output power during the activation reaction is 500-800W.

7. The method for preparing porous carbon particles with high ethane selectivity according to claim 1, characterized in that: In the step 2, the microwave irradiation time is 10-30 min.

8. A porous carbon particle with high ethane selectivity, characterized in that: The preparation method according to claim 1 is used for preparation.

9. The porous carbon particles with high ethane selectivity as claimed in claim 8 are used for adsorption and separation of ethane / ethylene mixed gas.

10. The porous carbon particles with high ethane selectivity according to claim 9 are used for adsorption and separation of ethane / ethylene mixed gas, characterized in that: The porous carbon particles have the characteristic of preferentially adsorbing ethane, that is, under the conditions of 25° C. and 1.0 bar, the adsorption selectivity of the porous carbon particles to an equimolar ethane / ethylene mixed gas is as high as 3.97, and the adsorption capacity of ethane reaches 3.07 mmol / g.